2000
DOI: 10.1002/(sici)1099-0682(200002)2000:2<375::aid-ejic375>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Pentacoordination at Fluoro-Substituted Silanes by Weak Lewis Donor Addition

Abstract: Quantum chemical calculations at the ab initio level indicate that Lewis donors such as amine or water form weak donor–acceptor complexes with fluoro‐substituted silanes. The strength of the donor–acceptor formation increases with increasing degree of fluorine substitution. Amine and water form strong adducts only for tetrafluorosilane. The higher element homologues of Lewis donors, such as phosphane and sulfur dihydride, do not in essence coordinate. A considerable role in donor–acceptor formation is exerted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
(3 reference statements)
2
15
0
Order By: Relevance
“…For example, early work suggested that tetrafluorosilane was bound to ammonia more tightly than unsubstituted silane [ 63 ]. This conclusion was confirmed in later calculations confined to Si [ 64 , 65 ] as well as in the other works that extended to complexes containing heavier tetrel atoms [ 31 , 66 ], and is consistent with our own findings above.…”
Section: Resultssupporting
confidence: 92%
“…For example, early work suggested that tetrafluorosilane was bound to ammonia more tightly than unsubstituted silane [ 63 ]. This conclusion was confirmed in later calculations confined to Si [ 64 , 65 ] as well as in the other works that extended to complexes containing heavier tetrel atoms [ 31 , 66 ], and is consistent with our own findings above.…”
Section: Resultssupporting
confidence: 92%
“…The tetrel family of atoms, headed by C and Si, also appear able to serve in this capacity [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . These sorts of bonds appear to be important in a number of processes including chemical reactions, molecular recognition, and the structure of materials [41][42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…32 The Lewis acidity of the silane is increased with increasing of the number of fluorine atoms at silicon. 39 Similarly, the number of fluorine atoms at silicon in the series of (O-Si)chelated amides of carboxylic acids (C) influences significantly the amount of the intramolecular C O→Si bond formation. 32 An intramolecular P O→Si interaction in compound 4 is absent, showing that the Lewis acidity of silicon is less important.…”
Section: Resultsmentioning
confidence: 99%